Advanced exergy analysis of an integrated energy storage system based on transcritical CO2 energy storage and Organic Rankine Cycle. (15th July 2020) - Zhang, Yuan; Liang, Tianyang; Yang, Chao; Zhang, Xuelai; Yang, Ke
Highlights: An integrated energy storage system was thermodynamically analyzed. Conventional and advanced exergy analyses were conducted. Conventional exergy analysis showed that LRHE should be firstly improved. Advanced exergy analysis revealed that ROHE should be firstly improved. The exergy efficiency difference between real and unavoidable conditions was 9.22%. Abstract: In this paper, an integrated energy storage system based on transcritical CO2 energy storage and Organic Rankine Cycle (ORC) is proposed. The working fluid of ORC cycle is R290 and the cold energy of LNG is utilized as the heat sink. The performance of the system is analyzed using conventional and advanced exergy analyses. The conventional exergy analysis quantifies the exergy destruction of each component independently and showed the exergy destruction of LRHE was the largest. The advanced exergy analysis considers the interconnections among the components of the system and the technical limitations of each component, which can reveal more valuable information. The results showed that the R290-Thermal oil heat exchanger had the greatest potential for improvement due to the largest avoidable exergy destruction rate of 171.679 kW. The unavoidable exergy destruction rate of the LNG-R290 heat exchanger was the largest, sharing 35.66% of total unavoidable exergy destruction. A comparison between the results of the two analysis methods showed the advanced exergy analysis gave more reasonable suggestions in terms of system optimization. Besides, the system exergy efficiency was 34.62% under real condition and the theoretical maximum for unavoidable condition was 43.48%, meaning great potential for the improvement of system performance.